Saint Yared’s Cosmic Harmony: Music, Astronomy, and Philosophy in 6th-Century Ethiopia - Belay Sitotaw Goshu (Budapest International Research and Critics University, 2025)
Saint Yared, a 6th-century Ethiopian composer, pioneered musical notation with his melekket system and Deggua antiphonary, yet his interdisciplinary contributions remain underexplored in global scholarship. This study investigates Yared’s integration of music, astronomy, and philosophy, aiming to reposition his legacy within world musicology and intellectual history. Methods: Employing qualitative methods, the research analyzes Ge’ez manuscripts, ethnomusicological recordings, and historical records through textual interpretation, comparative analysis, and thematic synthesis. It examines Deggua’s seasonal structure, the theological underpinnings of Yared’s modes (Ge’ez, Ezel, and Araray), the melekket system’s synthesis, Aksumite and Nine Saints’ influences, and Yared’s global context. Yared’s Deggua aligns with celestial cycles, reflecting astronomical knowledge, while his modes embody Trinitarian theology and Neoplatonic harmony. The notation predates European systems, integrating diverse disciplines shaped by Aksumite traditions and Byzantine thought via the Nine Saints. His work challenges Eurocentric narratives, predating Guido d’Arezzo and paralleling Boethius. Yared emerges as a visionary whose cosmic harmony unites science, art, and faith, affirming Ethiopia’s role in early intellectual history and warranting broader recognition. His contributions prefigure medieval developments, enriching global understanding of musicology’s origins. Future research should digitize Yared’s works, compare them with Asian notations, and integrate his legacy into educational curricula to enhance preservation and appreciation.